2015
DOI: 10.1182/blood-2015-03-636670
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of class II PI3K-C2α in platelet membrane morphology

Abstract: Key Points• PI3K-C2a controls platelet membrane structure and remodeling.• PI3K-C2a is a key regulator of a basal housekeeping PI3P pool in platelets.The physiologic roles of the class II phosphoinositide 3-kinases (PI3Ks) and their contributions to phosphatidylinositol 3-monophosphate (PI3P) and PI(3,4)P 2 production remain elusive. Here we report that mice heterozygous for a constitutively kinase-dead PI3K-C2a display aberrant platelet morphology with an elevated number of barbell-shaped proplatelets, a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
78
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 39 publications
9
78
0
1
Order By: Relevance
“…We and others have previously shown that platelets from PI3KC2a-deficient mice exhibit an increased surface area occupied by the channels of the OCS in TEM images [6,8]. We showed that PI3KC2a deficiency leads to an ultrastructural change in platelets that is limited to the internal membrane (OCS) of these cells.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…We and others have previously shown that platelets from PI3KC2a-deficient mice exhibit an increased surface area occupied by the channels of the OCS in TEM images [6,8]. We showed that PI3KC2a deficiency leads to an ultrastructural change in platelets that is limited to the internal membrane (OCS) of these cells.…”
Section: Discussionmentioning
confidence: 66%
“…As a result, the significant reduction in platelet deposition in this system using blood from PI3KC2a mice may suggest that PI3KC2a is important for the earliest stages of platelet adhesion, where membrane tethers, presumably derived from the OCS, are pulled from platelets without detectable cell activation via an interaction between von Willebrand factor and the platelet adhesion receptor GPIba [17]. The surprising lack of effect of PI3KC2a deficiency in standard assays of agonist-induced in vitro platelet function [6,8] supports this hypothesis. Alternatively, PI3KC2a may be involved in the subsequent propagation of platelet aggregates, since incoming platelets that tether to the surface of forming thrombi are discoid and demonstrate low levels of activation markers and minimal calcium flux, in sharp contrast to the initial core of the thrombus where platelets are generally fully activated [12,18].…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations